Environment-friendly ultra-high performance concrete as well as preparation method and application thereof

By replacing sugarcane ash and wood ash with wood ash instead of cement, the problems of complex ultra-high performance concrete raw materials and unenvironmental agricultural solid waste treatment are solved, and high-performance, low-cost and environmentally friendly concrete preparation is achieved.

CN119461993APending Publication Date: 2025-02-18HENAN ZHENGDA BUILDING MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411619429.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing ultra-high performance concrete raw materials are complex and difficult to prepare, resulting in high engineering cost and the incineration or landfill method of treating agricultural solid waste is not environmentally friendly.

Method used

Sugar cane ash and wood ash are used to partially replace cement, and its high activity and porous structure are used as auxiliary cementitious materials to reduce cement consumption and reduce production costs.

Benefits of technology

It achieves low energy consumption, low carbon emission, low shrinkage and low cost of ultra-high performance concrete, improves compressive and flexural strength, and effectively reduces the self-shrinkage of concrete, which is in line with the concept of sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461993A_ABST
    Figure CN119461993A_ABST
Patent Text Reader

Abstract

The invention provides environment-friendly ultra-high performance concrete and a preparation method and application thereof, and relates to the technical field of cement-based composite materials, and the environment-friendly ultra-high performance concrete is prepared from the following components in parts by weight: 570 to 610 parts of cement, 100 to 140 parts of plant ash, 105 to 140 parts of sugarcane ash, 155 to 165 parts of mineral powder, 80 to 90 parts of silicon powder, 1100 to 1200 parts of quartz sand, 185 to 195 parts of water, 11.2 to 12.5 parts of water reducing agent and 150 to 170 parts of steel fiber. The technical problems that traditional ultra-high performance concrete is large in self-constriction, large in cement consumption, high in production cost and not suitable for sustainable development are solved, and the technical effects of being high in compressive strength and breaking strength, small in early-stage self-constriction and beneficial to environmental protection are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cement-based composite materials, and in particular to an environmentally friendly ultra-high performance concrete and a preparation method and application thereof. Background Art

[0002] Ultra-high performance concrete (UHPC) is a new type of cement-based composite material with excellent mechanical properties and durability. Its application in engineering structures with special requirements for concrete is growing rapidly. However, the complex and diverse raw materials of UHPC and the difficulty in preparation lead to high project costs, which seriously affects its promotion and application.

[0003] At present, my country produces a large amount of agricultural solid waste every year, among which the annual output of bagasse and wood ash is about 500,000 tons. These agricultural solid wastes are often treated by incineration or landfill. However, incineration or landfill not only consumes a lot of saved land, but also easily produces a lot of pollution, which is not conducive to environmental protection.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] One of the purposes of the present invention is to provide an environmentally friendly ultra-high performance concrete, which not only has lower energy consumption and carbon emissions, but also has the advantages of ultra-high performance, low shrinkage and low cost.

[0006] The second object of the present invention is to provide a method for preparing an environmentally friendly ultra-high performance concrete, which has a simple process and is highly efficient.

[0007] The third object of the present invention is to provide an application of an environmentally friendly ultra-high performance concrete, which conforms to the concept of sustainable development and can improve the performance of building materials.

[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0009] In a first aspect, an environmentally friendly ultra-high performance concrete comprises the following components by weight:

[0010] 570-610 parts of cement, 100-140 parts of wood ash, 105-140 parts of sugarcane ash, 155-165 parts of mineral powder, 80-90 parts of silica powder, 1100-1200 parts of quartz sand, 185-195 parts of water, 11.2-12.5 parts of water reducer, and 150-170 parts of steel fiber.

[0011] Furthermore, the wood ash includes calcined wood ash.

[0012] Furthermore, the particle size of the wood ash is below 75 μm.

[0013] Furthermore, the sugarcane ash includes calcined sugarcane ash.

[0014] Furthermore, the particle size of the sugarcane ash is below 75 μm.

[0015] Furthermore, the calcination temperature is 750-850°C.

[0016] Furthermore, the compressive strength of the environmentally friendly ultra-high performance concrete is above 130 MPa;

[0017] Preferably, the flexural strength of the environmentally friendly ultra-high performance concrete is above 25 MPa.

[0018] Furthermore, the early autogenous shrinkage of the environmentally friendly ultra-high performance concrete is within 700 μm / m.

[0019] In a second aspect, a method for preparing the environmentally friendly ultra-high performance concrete as described in any one of the above items comprises the following steps:

[0020] The components are mixed in proportion and formed to obtain the environmentally friendly ultra-high performance concrete.

[0021] A third aspect provides an application of the environmentally friendly ultra-high performance concrete described in any one of the above items in building materials.

[0022] Compared with the prior art, the present invention has at least the following beneficial effects:

[0023] The environment-friendly ultra-high performance concrete provided by the present invention comprises sugarcane ash and wood ash which are mixed to partially replace cement. The sugarcane ash and wood ash have a high silicon content and are highly active. In particular, the sugarcane ash will produce a large amount of amorphous oxides after calcination and is porous inside. Therefore, the two can be used as auxiliary cementitious materials to replace cement, which can not only effectively reduce the amount of cement and significantly reduce the production cost, but also effectively reduce the self-shrinkage of concrete and improve the performance of concrete. At the same time, a large amount of sugarcane ash and wood ash are also effectively processed, which is in line with the concept of sustainable development. The ultra-high performance concrete of the present invention can achieve a compressive strength of more than 130 MPa, a flexural strength of about 25 MPa, and an early self-shrinkage controlled within 700 μm / m through the mixed mixing of components such as cement, mineral admixtures, quartz sand, wood ash and sugarcane ash under the synergistic effect of each component and its weight ratio.

[0024] The method for preparing the environmentally friendly ultra-high performance concrete provided by the invention has simple process and high efficiency.

[0025] The application of the environmentally friendly ultra-high performance concrete provided by the present invention complies with the concept of sustainable development and can improve the performance of building materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 This is the autogenous shrinkage curve of the concrete of Examples 1-5 obtained in Test Example 1 of the present invention. DETAILED DESCRIPTION

[0028] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] According to a first aspect of the present invention, there is provided an environmentally friendly ultra-high performance concrete comprising the following components in parts by weight:

[0030] 570-610 parts of cement, 100-140 parts of wood ash, 105-140 parts of sugarcane ash, 155-165 parts of mineral powder, 80-90 parts of silica powder, 1100-1200 parts of quartz sand, 185-195 parts of water, 11.2-12.5 parts of water reducer, and 150-170 parts of steel fiber.

[0031] In the present invention, typical but non-limiting weight portions of cement are, for example, 570 parts, 580 parts, 590 parts, 600 parts, and 610 parts; typical but non-limiting weight portions of wood ash are, for example, 100 parts, 110 parts, 120 parts, 130 parts, and 140 parts; typical but non-limiting weight portions of sugarcane ash are, for example, 105 parts, 110 parts, 115 parts, 120 parts, 125 parts, 130 parts, 135 parts, and 140 parts; typical but non-limiting weight portions of mineral powder are, for example, 155 parts, 160 parts, and 165 parts; typical but non-limiting weight portions of silica powder are, for example, 80 parts, 82 parts, 84 parts, 86 parts, 88 parts, and 90 parts; typical but non-limiting weight portions of quartz sand are, for example, 1100 parts , 1120 parts, 1140 parts, 1160 parts, 1180 parts, 1200 parts; typical but non-limiting weight portions of water are, for example, 185 parts, 186 parts, 187 parts, 188 parts, 189 parts, 190 parts, 191 parts, 192 parts, 193 parts, 194 parts, 195 parts; typical but non-limiting weight portions of water reducer are, for example, 11.2 parts, 11.3 parts, 11.4 parts, 11.5 parts, 11.6 parts, 11.7 parts, 11.8 parts, 11.9 parts, 12 parts, 12.1 parts, 12.2 parts, 12.3 parts, 12.4 parts, 12.5 parts; typical but non-limiting weight portions of steel fiber are, for example, 150 parts, 155 parts, 160 parts, 165 parts, 170 parts.

[0032] The environment-friendly ultra-high performance concrete provided by the present invention comprises sugarcane ash and wood ash mixed together to partially replace cement. The sugarcane ash and wood ash have a high silicon content and are highly active. In particular, the sugarcane ash will produce a large amount of amorphous oxides after calcination and is porous inside. Therefore, the two can be used as auxiliary cementitious materials to replace cement. This can not only effectively reduce the amount of cement used and significantly reduce production costs, but also effectively reduce the self-shrinkage of concrete and improve the performance of concrete. At the same time, a large amount of sugarcane ash and wood ash can be effectively processed, which is in line with the concept of sustainable development.

[0033] The ultra-high performance concrete of the present invention, through the composite admixture of components such as cement, mineral admixtures, quartz sand, wood ash and sugarcane ash, can achieve a compressive strength of more than 130 MPa, a flexural strength of about 25 MPa, and an early self-shrinkage controlled within 700 μm / m under the synergistic effect of each component and its weight ratio.

[0034] In the present invention, wood ash includes but is not limited to calcined wood ash, and sugarcane ash includes but is not limited to calcined sugarcane ash.

[0035] Sugarcane ash and wood ash have a high silicon content and are highly active. In particular, when sugarcane ash is calcined at a certain temperature, it will produce a large amount of amorphous oxides and is porous inside. Therefore, it can be used as an auxiliary cementitious material to replace cement, which can effectively reduce the shrinkage of concrete. Specifically, the high activity and porous structure of sugarcane ash and wood ash can be used to partially replace cement, which can release free water during the curing process to reduce internal shrinkage and promote cement hydration, thereby achieving the effect of inhibiting shrinkage.

[0036] In a preferred embodiment, the temperature of calcining wood ash can be 750-850°C, and typical but non-limiting temperatures are, for example, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, 810°C, 820°C, 830°C, 840°C, and 850°C.

[0037] In the present invention, the temperature of calcining wood ash is controlled within an appropriate range to achieve the expected calcination effect; if the temperature of calcining wood ash is too high, it will destroy the original structure and reduce its internal activity; if the temperature of calcining wood ash is too low, it will not be able to fully stimulate the internal activity.

[0038] In a preferred embodiment, the temperature of calcining sugarcane ash can be 750-850°C, and typical but non-limiting temperatures are, for example, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, 810°C, 820°C, 830°C, 840°C, and 850°C.

[0039] In the present invention, the temperature of calcining sugarcane ash is controlled within an appropriate range to achieve the expected calcination effect. If the temperature of calcining sugarcane ash is too high, the original structure will be destroyed and the internal activity will be reduced; if the temperature of calcining sugarcane ash is too low, the internal activity will not be fully stimulated.

[0040] In a preferred embodiment, the particle size of wood ash can be below 75 μm, and the particle size of sugarcane ash can be below 75 μm. The particle sizes of wood ash and sugarcane ash are within this range, which is more conducive to improving the synergistic effect between the two, and is more conducive to further reducing the shrinkage of concrete and further improving the performance of concrete.

[0041] In the present invention, sugarcane ash and plant ash can achieve a synergistic effect. Sugarcane ash and plant ash are first calcined at a high temperature of 750 to 850° C. and then screened to obtain particles with a diameter of less than 75 μm for composite mixing to replace cement. This can effectively reduce the shrinkage of concrete and improve the performance of concrete. In particular, when the amount of sugarcane ash added is 130 parts and the amount of plant ash added is 120 parts to replace the amount of cement, the various properties of ultra-high performance concrete (UHPC) can reach an optimal state.

[0042] In a preferred embodiment, the compressive strength of the environmentally friendly ultra-high performance concrete of the present invention can be above 130 MPa, the flexural strength can be above 25 MPa, and the early autogenous shrinkage can be controlled within 700 μm / m.

[0043] The environmentally friendly ultra-high performance concrete provided by the present invention partially replaces cement by the composite admixture of sugarcane ash and wood ash. Under the synergistic effect of various components and their weight ratios, on the basis of ensuring various performances, not only the production cost is effectively reduced, but also the compressive and flexural strengths are improved, and the self-shrinkage of the concrete is also effectively reduced.

[0044] According to a second aspect of the present invention, there is provided a method for preparing the environmentally friendly ultra-high performance concrete as described in any one of the above, comprising the following steps:

[0045] The components are mixed in proportion and formed to obtain environmentally friendly ultra-high performance concrete.

[0046] The method for preparing the environmentally friendly ultra-high performance concrete provided by the invention has simple process and high efficiency.

[0047] According to a third aspect of the present invention, there is provided a use of any one of the environmentally friendly ultra-high performance concrete in building materials.

[0048] The application of the environmentally friendly ultra-high performance concrete provided by the present invention complies with the concept of sustainable development and can improve the performance of building materials.

[0049] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.

[0050] Examples 1-5

[0051] Example 1-5 provides an environmentally friendly ultra-high performance concrete, and the components and their weight ratios are shown in Table 1.

[0052] Among them, cement is ordinary Portland cement; the particle size of mineral powder is 325 mesh; the average particle size of silica powder is about 1000 mesh; the particle size of quartz sand is 40-120 mesh; the water reducer is polycarboxylic acid high-efficiency water reducer with a water reduction rate of more than 40%; the length of steel fiber is 13mm and the diameter is 0.22mm.

[0053] Sugarcane ash is calcined sugarcane ash, which is prepared by the following preparation method:

[0054] Sugarcane ash is first calcined at 750-850°C for 1 hour, and then ball-milled for 1 hour to sieve out particles with a size of less than 75 μm to obtain calcined sugarcane ash;

[0055] The plant ash is calcined plant ash, which is prepared by the following preparation method:

[0056] The wood ash is first calcined at a high temperature of 750-850°C for 1 hour, and then ball-milled for 1 hour to sieve out particles with a diameter of less than 75 μm to obtain calcined wood ash.

[0057] Table 1

[0058]

[0059] Example 6

[0060] The difference between this embodiment and embodiment 4 is that the calcination temperature of the wood ash in this embodiment is 700°C, and the rest is the same as embodiment 4, and the concrete obtained has the defect that the volcanic ash activity inside the wood ash cannot be fully stimulated.

[0061] Example 7

[0062] The difference between this embodiment and embodiment 4 is that the calcination temperature of the wood ash in this embodiment is 900°C, and the rest is the same as embodiment 4, and the obtained concrete has the defect that the silicon oxide structure morphology inside the wood ash is destroyed, resulting in reduced activity.

[0063] Example 8

[0064] The difference between this embodiment and embodiment 4 is that the calcination temperature of sugarcane ash in this embodiment is 700° C., and the rest is the same as embodiment 4. The concrete obtained has the defect that the volcanic ash activity inside the sugarcane ash cannot be fully stimulated.

[0065] Example 9

[0066] The difference between this embodiment and embodiment 4 is that the calcination temperature of sugarcane ash in this embodiment is 900° C., and the rest is the same as embodiment 4. The concrete obtained has the defect that the silicon oxide structure morphology inside the sugarcane ash is destroyed, resulting in reduced activity.

[0067] Example 10

[0068] This embodiment is a method for preparing the environmentally friendly ultra-high performance concrete of Embodiments 1-9, comprising the following steps:

[0069] The components are mixed in proportion and formed to obtain environmentally friendly ultra-high performance concrete.

[0070] Comparative Examples 1-5

[0071] The difference between Comparative Examples 1-5 and Example 4 is that the weight ratios of the components are different, see Table 2, and the rest are the same as Example 4 to obtain concrete.

[0072] Table 2

[0073]

[0074] Test Example 1

[0075] The test results of concrete of each embodiment and comparative example are shown in Table 3, and the autogenous shrinkage curves are shown in Figure 1 .

[0076] Test method:

[0077] The size of the compressive strength test piece is 100mm×100mm×100mm, and a 2000KN electro-hydraulic pressure testing machine is used with a loading speed of 1.2MPa / s;

[0078] The flexural strength was tested using a 100mm×100mm×400mm prism specimen using a universal testing machine in a displacement-controlled loading mode with a loading speed of 0.2mm / min;

[0079] The shrinkage test was carried out in accordance with GB / T 50082-2009 “Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete”. The test was carried out with a mold under constant temperature and humidity conditions. The temperature was maintained at (20±2)℃ and the relative humidity was (60±5)%. The specimen size was 100mm×100mm×515mm, with 3 specimens in each group.

[0080] Table 3

[0081]

[0082] In summary, the environmentally friendly ultra-high performance concrete provided by the present invention partially replaces cement by the compounding of sugarcane ash and wood ash. Under the synergistic effect of each component and its weight ratio, on the basis of ensuring various performances, it not only effectively reduces the production cost, but also improves the compressive and flexural strength, and also effectively reduces the shrinkage of concrete.

[0083] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. An environmentally friendly ultra-high performance concrete, characterized in that: The composition comprises the following components in parts by weight: 570-610 parts of cement, 100-140 parts of wood ash, 105-140 parts of sugarcane ash, 155-165 parts of mineral powder, 80-90 parts of silica powder, 1100-1200 parts of quartz sand, 185-195 parts of water, 11.2-12.5 parts of water reducer, and 150-170 parts of steel fiber.

2. The environmentally friendly ultra-high performance concrete according to claim 1, characterized in that: The wood ash includes calcined wood ash.

3. The environmentally friendly ultra-high performance concrete according to claim 2, characterized in that: The particle size of the wood ash is below 75 μm.

4. The environmentally friendly ultra-high performance concrete according to claim 1, characterized in that: The sugarcane ash includes calcined sugarcane ash.

5. The environmentally friendly ultra-high performance concrete according to claim 4, characterized in that: The particle size of the sugarcane ash is below 75 μm.

6. The environmentally friendly ultra-high performance concrete according to any one of claims 1 to 5, characterized in that: The calcination temperature is 750-850°C.

7. The environmentally friendly ultra-high performance concrete according to any one of claims 1 to 5, characterized in that: The compressive strength of the environmentally friendly ultra-high performance concrete is above 130 MPa; Preferably, the flexural strength of the environmentally friendly ultra-high performance concrete is above 25 MPa.

8. The environmentally friendly ultra-high performance concrete according to claim 7, characterized in that: The early-stage autogenous shrinkage of the environmentally friendly ultra-high performance concrete is within 700 μm / m.

9. A method for preparing the environmentally friendly ultra-high performance concrete according to any one of claims 1 to 8, characterized in that: The following steps are involved: The components are mixed in proportion and formed to obtain the environmentally friendly ultra-high performance concrete.

10. Use of the environmentally friendly ultra-high performance concrete according to any one of claims 1 to 8 in building materials.